ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PENGGUNAAN INTERNET SERVICE PROVIDER (ISP) SMARTFREN DI SEMARANG (STUDI PADA MAHASISWA EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO) - Ardiansyah, Said Muhammad Reza; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2013)
This study aims to determine the effect of brand equity on buying decisions. The independent variable of this study are Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty. This study uses Â consumers buying decision as the dependent variable.This research was motivated by the phenomenon of inter-brand competition that enliven the market, especially for products internet service provider (ISP). Population of this research is students of the Economic and Bussines Faculty UNDIP who use internet service provider (ISP) Smartfren brand. This study uses purposive sampling method. The number of sample is 100 respondent. Data analisys model used was multiple linier regresion analisys. The test Â used in this study include,validity test, reliability test, and classic assumption test. Â Hypothesis test uses, t test, F test, and the coefficient of determination (R2).The elements of brand equity in this research are brand awareness, brand associations, perceived quality, and brand loyalty. Brand awareness is the independent variable that has the most impact on consumer buying decisions with the coefficient of 0.323. This indicates that product Smartfren known, so with a high level of brand awareness costumers has a godd will on buying decisions he had made. The higher level of consumer awareness of product data service provider brand Smartfren the more powerful influence consumers to make buying decisions on products data service providers such Smartfren brand.